Assessment of the Consumption Pattern of Household Insecticides in Mazandaran Province - Nastaran Asgari; Fathollah Gholami-Borujeni (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: An awareness of the pattern of using household insecticides in order to determine the type of damage caused by them, how to use household insecticides, the necessary safety measures in using insecticides, determining strategies to reduce the harmful effects of insecticides are of utmost importance. This descriptive study investigated the consumption pattern of household insecticides in Mazandaran province in 2022. Methods: For this purpose, 380 subjects living in Mazandaran province were selected via random sampling from people who had access to social networks. In order to assess the consumption pattern, a standard questionnaire was used whose validity and reliability were checked and confirmed. Results: The results demonstrated that the most widely used household insecticide in Mazandaran province was Halak (Samsaline). Moreover,  the reason for using household pesticides (0.17), the frequency of using pesticides (0.20), the intensity of using pesticides (0.04), and the advertisement of pesticides (how to get acquainted) (0.07) had a positive and significant effect on the amount of pesticides consumption (P<0.05). The most common use of insecticides in the Mazandaran province was to control mosquitoes (33.7%), and 41.7% of household insecticides were used as sprays. Conclusion: As evidenced by the results of this study, an awareness of the harms and chemicals present in these pesticides for the health of humans and pets and the safety measures required during use are among the most important factors that affect the consumption pattern of household pesticides in Mazandaran province.